Local atomic structure of thin and ultrathin films via rapid high-energy X-ray total scattering at grazing incidence. (2019) - Dippel, Ann-Christin; Roelsgaard, Martin; Boettger, Ulrich; Schneller, Theodor; Gutowski, Olof; Ruett, Uta
No abstract available